THE MAGNETIC FABRIC OF SOME LOESS/PALAEOSOL DEPOSITS - Hus J.J. (My University, 2003)
The magnetic fabric of loess–palaeosol deposits in Asia, Europe and Siberia, from different sources and spanning different time intervals is examined in this paper. Magnetic fabric was visualised by measuring the anisotropy of magnetic susceptibility (AMS) of hand-cut samples. The fabric ellipsoids support a bedding-parallel foliation with low lineation in all cases. Maximum susceptibility directions in the upper part of the Wucheng formation on the Loess Plateau of China, confined to the bedding plane, are biased towards a preferential direction (prevailing palaeowind direction?). Soil formation results in decreasing degree of anisotropy and foliation, and in some cases in large deviations of the principal susceptibility directions caused by bioturbation. The orientation of the ferromagnetic fraction was obtained separately, for a limited number of loess–soil couplets, by measuring the anisotropy of anhysteretic remanent magnetization. The two-component model or regression line method of [Tectonophysics 91 (1983) 165], to separate the ferromagnetic AMS from the bulk AMS, was applied to samples with low and high magnetic susceptibilities from loess sections in Belgium and Siberia. The magnetic fabric of loess is composite, mainly reflecting the preferred alignment of crystallo-graphic lattices of phyllosilicates and of shape-oriented multidomain magnetites.